2010
DOI: 10.1089/thy.2010.0177
|View full text |Cite
|
Sign up to set email alerts
|

Age Modifies the Response to Recombinant Human Thyrotropin

Abstract: Both days 3 and 5 TSH concentrations were higher in older individuals after rhTSH administration. This finding did not appear to be related to body weight, body mass index, or glomerular filtration rate in a simple manner. The TSH concentration achieved may be a result of complex interactions between distribution within fat and muscle body compartments, hepatic function, and renal function. Prospective studies could examine whether the magnitude of the TSH elevation after rhTSH administration affects diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
4
15
1
Order By: Relevance
“…Furthermore, by help of the stepwise forward multiple linear regression, these parameters were weighted according to their effect size on the prediction of the depending variable peak TSH with BSA and renal function as most relevant followed by age, sex, and height ( Fig. 2A) (11)(12)(13). Regarding the impact of sex, our findings corroborated the data of Montesano et al and Castagna et al, even if the latter did not test sex by multivariate means (10,11).…”
supporting
confidence: 88%
See 4 more Smart Citations
“…Furthermore, by help of the stepwise forward multiple linear regression, these parameters were weighted according to their effect size on the prediction of the depending variable peak TSH with BSA and renal function as most relevant followed by age, sex, and height ( Fig. 2A) (11)(12)(13). Regarding the impact of sex, our findings corroborated the data of Montesano et al and Castagna et al, even if the latter did not test sex by multivariate means (10,11).…”
supporting
confidence: 88%
“…The results of the two patients from our study who also demonstrated a severely impaired renal function further support the proposition of a direct impact of kidney function on the blood TSH concentration after rhTSH as the one who is on hemodialysis presented with a creatinine of 7.4 mg/dL (GFR 7.9 mL/1.73 m 2 per minute) and a concomitant peak TSH of 385.9 mU/L, while the other demonstrated a creatinine of 4.1 mg/dL (GFR 10.6 mL/1.73 m 2 per minute) and a TSH of 196.0 mU/L. However, the other studies systematically investigating the influence of renal function on the resulting peak TSH failed to demonstrate any significant correlation by means of multivariate comparisons (11,12). Over et al found a positive correlation in their univariate analysis that was no longer significant applying multivariate statistics (12).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations